Odyssey : Books XVII-XVIII - Homer; Steiner, Deborah, 1960- (Cambridge, UK. : Cambridge University Press, 2010)
'Books XVII and XVIII of the Odyssey feature, among other episodes, the disguised Odysseus' penetration of his home after an absence of twenty years and his first encounter with his wife. The commentary provides linguistic and syntactical guidance suitable for upper-level students along with detailed consideration of Homer's compositional and narrative techniques, his literary artistry and the poem's central themes. An extensive introduction considers questions of formulaic composition, the nature of the poem's audience and the context of its performance, and isolates the concerns most prominent in the poem's second half and in Books XVII and XVIII in particular. Here too are considered the roles of Penelope and Telemachus, questions of disguise and recognition, and the institution of hospitality flaunted by the suitors in Odysseus' halls. Brief sections also discuss Homeric metre and the transmission of the text'--
'Homer's Odyssey tells a familiar story: a hero, a veteran of the Trojan War, returns home after ten trial-filled years of wandering in exotic lands only to find his halls occupied by 108 carousing youths who court his wife in the hope that the lawful husband and master has perished abroad. And yet for all the simplicity of its tale, the poet's technique is brilliantly intricate; from the notorious tease of the opening line which hides the epic hero's name, to the sudden threat of retaliation from the dead suitors' kin in the closing episode, the composition uses flashbacks and internal narratives, dramatic irony, doubling, and retardation devices to keep us wondering how exactly affairs in Ithaca will be resolved. It is a work that, not surprisingly, has exercised a lasting fascination from archaic through to contemporary times, and that has been re-imagined in countless forms, visual, verbal and musical among them. If another study of the Odyssey needs no justification, then the choice to focus on books 17 and 18may prompt the question'why these?'One reason is the sheer diversity and tonal range of the two books' contents, which run from the burlesque comedy of the boxingmatch between the disguised Odysseus and the parasite Irus to the charged moment when the hero re-enters his home after his twenty years' absence and first sets eyes on his wife. The pathos of the death of the tick-infested Argus, who has kept vigil for his master ever since his departure, is unmistakable, its poignancy sharpened by the entirely different episode preceding it, where Odysseus meets the churlish cowherd Melanthius and is treated to language and threats normally excluded from the epic register'--
Includes bibliographical references (p. 220-234) and index.
Text in Greek; editorial matter in English.
Keywords: Odysseus (Greek mythology) -- Poetry